How South African SMES can become better candidates for export finance - Matthee, Marianne (Managing global transitions, 2013)
SMES are considered to be important drivers of economic growth and development throughout the world but to deliver true economic benefits, they need to grow into sustainable, profitable businesses. Expanding into foreign markets provides an excellent vehicle for growth but many hurdles stand in the way of SMES making the transition from local to international. The difficulty associated with obtaining finance for export market development is a key stumbling block. Financial institutions regard SMES as high risk because they have limited resources and capacity, and are more likely to default than larger concerns. This paper examines the various risks that financial institutions in South Africa assess when they receive applications for export finance from SMES. What makes this study different is that it offers perspectives on export risks from the lenders point of view a hitherto neglected area of research. The findings are packaged as a set of guidelines on how SMES can mitigate these risks and improve their chances of securing the financial assistance that has often eluded them in the past.
Keywords: mala podjetja; small and medium sized enterprises; srednja podjetja; internationalisation; export finance; internacionalizacija; izvoz; risk mitigation; financiranje izvoza; blažitev tveganj; SME